ANALISIS KOMPONEN BUKU TEKS BAHASA INDONESIA KELAS XI KURIKULUM 2013 TERBITAN GRAFINDO - Anggi Nur Febriani; Nurul Aisyah Syahkila; Safira Ayesha Ismaidini; Inayah Hanum; Safinatul Hasanah Harahap (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to determine (1) the appropriateness of the content, (2) the appropriateness of the language, and (3) the graphics of the Indonesian language student textbook for the 2013 Curriculum Revised Edition for Class XI SMA/MA/SMK/MAK published by Grafindo Media Pratama. The type of research used in this research is qualitative descriptive research. The research instruments used in this research are indicators from the observed aspects which include the appropriateness of the material, language and graphics. The data collection technique used is the note-taking technique. The data analysis techniques used consist of identifying, classifying, interpreting and concluding. The results of this research prove that the revised edition of the 2013 Curriculum Indonesian language student textbook for Class XI SMA/MA/SMK/MAK published by Grafindo Media Pratama for class text and is good for use to support Indonesian language learning in the 2013 curriculum which is still used in several schools, especially for class XI students.